Insights from Local Authorities for the Assessment of Urban Air Mobility Impacts - Santos, M.; Kalakou, S.; Ferreira, F. (Living and Walking in Cities: Smart Mobility and Shared Urban Spaces, 2025)
Urban Air Mobility (UAM) emerges as an innovative solution driven by technological advancements to address the challenges posed by urbanization and sustainability issues. As a key component of the future mobility sector, its successful integration depends on the perspectives of multiple stakeholders, particularly local authorities and aviation experts, who shape the UAM ecosystem and share responsibility for its implementation. However, while aviation professionals currently play a central role in shaping UAM, the involvement of local authorities remains limited despite their position as the ultimate decision-makers regarding the feasibility and deployment of UAM applications within their jurisdictions. This research explores the perspectives of local authorities on the development of UAM services, focusing on spatial-temporal planning and design. The findings highlight the diverse dimensions of UAM’s impact, including environmental and socioeconomic aspects, as well as concerns related to urban planning, regulation, safety and operations. Specific indicators identified include emissions, time savings, privacy and connectivity. By centering the perspectives of local authorities—often overlooked in existing UAM research—this study contrib utes to the literature by bridging the gap between aviation-centric and policy driven approaches. Practically, the results offer a structured framework for municipalities to assess UAM’s viability and inform urban planning strategies. Socially, the study underscores the importance of governance in fostering sustainable and accepted UAM implementations. These insights can guide policymakers, urban planners, and industry stakeholders in designing UAM solutions that align with local needs, regulatory frameworks, and broader sustainability goals.